The Effect of Maggot Meal as Fish Meal Substitute on Milkfish (Chanos chanos Forsskal) Growth and Survival Rate - S Sumaryam; Muhammad Tajuddin Noor; Didik Budiyanto; Gilang Rusrita Aida; Moh. Zainal Arifin (Demeter: Journal of Farming and Agriculture, 2023)
As one of the ten leading aquaculture commodities in Indonesia. The high demand for milkfish (Chanos chanos Forsskal) certainly requires a new alternative to fulfill feed ingredients in milkfish cultivation. Currently, the fish meal comes from imports and is quite expensive, despite being the main source of protein for farmed fish. Therefore, an alternative to the fish meal is needed to reduce production costs. One of them is maggot meal which has high availability and high protein. This study aims to examine maggot meal as fish meal substitutes effects on milkfish’s (Chanos chanos Forsskal) growth and survival. This study utilized the experimental method, using a Completely Randomized Design (CRD), and analyzed with ANOVA. The difference in treatment lies in the difference in the percentage of fish and maggot meal as the substitutes, divided into five treatments of 0%, 25%, 50%, 75%, and 100%. The parameters being observed include absolute weight gain, survival rate, and specific weight growth rate. The results illustrate highest average absolute weight growth was recorded in 0% maggot meal substitution, and the highest daily specific weight growth rate was in the treatment of substitution with 0% maggot meal. The greatest survival rate, there is a substitution of 25% maggot meal. ANOVA results illustrated no significant effect (P<0.05) on the growth of total weight, the growth rate of specific weight, and the milkfish (Chanos chanos Forsskal) survival rate from the maggot meal substitutes